Peranan Aparatur Desa dalam Meningkatkan Pengembangan Sumber Daya Manusia di Desa Mattirowalie Kabupaten Bulukumba - Supriyanto (PT. PENERBIT TIGA MUTIARA, 2023)
The village apparatus is an element of village government organizers who work professionally and proficiently in helping village heads carry out government duties and community interests so that government runs smoothly, especially in developing human resources in the village. Researchers want to know the role and performance of village apparatus in human resource development and identify factors that influence human resource development in Mattirowalie Village. With benefits, it can add better insight to the entire Mattirowalie Village apparatus. The qualitative research method is purposive sampling and the type of research is descriptive/survey with research informants as many as 8 village officials and 2 people from Mattirowalie Village. randomly selected and professional. Village apparatus data can be collected using observation, interview and documentation methods. This research shows the results that the role of village apparatus as organizers in the development of human resources (HR). The way of village apparatus in developing human resources in the village by implementing work discipline, improving education and good service to the community. Then there are 4 factors that affect the development of village apparatus resources: 1) Village head / leader, the village head is someone who has been directly selected by the community to be a good leader and is entrusted to be able to do good things that can be used as an example for the community. 2) Education, education is a process that can educate and improve the quality of human resources. 3) Training, training is a process of improving human resources by improving community skills. 4) Economy, economy is one of the drivers in increasing human resources in the village.